2018
DOI: 10.3390/md16080288
|View full text |Cite
|
Sign up to set email alerts
|

Blueprints for the Next Generation of Bioinspired and Biomimetic Mineralised Composites for Bone Regeneration

Abstract: Coccolithophores are unicellular marine phytoplankton, which produce intricate, tightly regulated, exoskeleton calcite structures. The formation of biogenic calcite occurs either intracellularly, forming ‘wheel-like’ calcite plates, or extracellularly, forming ‘tiled-like’ plates known as coccoliths. Secreted coccoliths then self-assemble into multiple layers to form the coccosphere, creating a protective wall around the organism. The cell wall hosts a variety of unique species-specific inorganic morphologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 93 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…[ 105 ] Coccolith biomineralization induced by coccolithophores produce extracellular coverings of CaCO 3 platelets. [ 110 ] The most common species include Emiliania huxleyi and Gephyrocapsa oceanica . Other species such as Coccolithus braarudii and Calcidiscus leptoporus are relatively less heavily calcified.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…[ 105 ] Coccolith biomineralization induced by coccolithophores produce extracellular coverings of CaCO 3 platelets. [ 110 ] The most common species include Emiliania huxleyi and Gephyrocapsa oceanica . Other species such as Coccolithus braarudii and Calcidiscus leptoporus are relatively less heavily calcified.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…Osteoporosis is a serious disease in the aged population which currently affects 200 million people worldwide and causes approximately 8.9 million fractures every year [41,42]. About 21.4% of postmenopausal women over the age of 50 may have osteoporosis, and 51.2% of them have significant bone mass loss [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have revealed that coccoliths are a small structure with higher risk to get damaged, especially during the sample preparation process 49, 54, 65, 66. Thus, that's making it highly difficult to study the complete structure of coccolithophore.…”
Section: Discussionmentioning
confidence: 99%